Cooper, Frank (London, 2011)
2011 "Cooper, Frank", 2011, HistoryTalk Frank was a sheet metal worker who, after 1945, worked in various 'shops' in London including Battersea, Wandsworth and Mitcham until he relocated to Ruislip after marrying Joan. He then worked in west London including Carrier's, ACI, at John Lyons, Benham's and MacDowell's. He earned 'good' money throughout through the period 1950- 1970 and there were many job opportunities with the growth of Heathrow Airport. He describes the changes to work and introduction of new technology and how working with other people is important. He later worked for the Northwest Thames Regional Health Authority.